Dinámica de la biomasa, carbono y CO2e del bosque de Varillal seco en la zona de amortiguamiento de la Reserva Nacional Alpahuayo - Mishana, Iquitos. Perú, periodo 2005-2017 - Morcera Pinedo, Abby Emira (2019)
In order to determine the dynamics of biomass, carbon and CO2e, a study was carried out in the high dry varillal forest of Iquitos, Peru under the principle of continuous forest inventory, during the period 2005 to 2017, using three permanent plots of one hectare each divided into 100 sub-plots of 10 x 10 m. The average at the end of the census period (2017), for aboveground biomass was 186.18±5.87 t/ha, for aboveground carbon it was 87.03±76 t/ha; for the carbon dioxide equivalent of trees above ground it was 320.85±10.12 tCO2e/ha and below ground it was 118.71±3.75 tCO2e/ha. The aboveground biomass in trees without lianas was 121.53±56,315 t/ha, and in trees with lianas that restrict their growth was 2.81 ± 5.14 t/ha. While the aboveground biomass of trees with regular crown was 99.57±62.88 t/ha, in those with irregular crown 36.09±40.39 t/ha. The annual growth rate of the average aboveground biomass in the period 2005 to 2007 was 7.85%, in the period 2007 to 2017 it was 4.05%, and between 2005 and 2017 it was 4.68%. Of the 102 species recorded in the censuses, six species contributed 51.16% of the total biomass, such as Dicymbe uaiparuensis (19.39%), Pachira brevipes (8.24%), Sloanea latifolia (7.76%), Caraipa utilis (5.46%), Tachigali bracteosa (5.17%) and Diplotropis purpurea (5.15%).